2010
DOI: 10.3354/cr00929
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the vulnerability of blanket peat to climate change using an ensemble of statistical bioclimatic envelope models

Abstract: ABSTRACT:We assessed the vulnerability of blanket peat to climate change in Great Britain using an ensemble of 8 bioclimatic envelope models. We used 4 published models that ranged from simple threshold models, based on total annual precipitation, to Generalised Linear Models (GLMs, based on mean annual temperature). In addition, 4 new models were developed which included measures of water deficit as threshold, classification tree, GLM and generalised additive models (GAM). Models that included measures of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 52 publications
4
76
0
Order By: Relevance
“…A previous study on peatland model intercomparisons suggests that the bioclimatic space associated with peat could decline considerably under a changing climate (Clark et al, 2010). The importance of high-latitude processes is further underlined by Stocker et al (2013), who show that annual CH 4 emissions from peatlands increase considerably (+120-200 %) until 2100 AD in the case of RCP 8.5.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A previous study on peatland model intercomparisons suggests that the bioclimatic space associated with peat could decline considerably under a changing climate (Clark et al, 2010). The importance of high-latitude processes is further underlined by Stocker et al (2013), who show that annual CH 4 emissions from peatlands increase considerably (+120-200 %) until 2100 AD in the case of RCP 8.5.…”
Section: Discussionmentioning
confidence: 84%
“…On the other hand, warmer temperatures enhance water loss through evaporation and transpiration, which in turn affects water table position and eventually NPP. This process seems to be an important factor for peatland modeling (Clark et al, 2010). In addition, warmer temperatures increase soil C decomposition and emissions of the greenhouse gases (GHG), including carbon dioxide (CO 2 ) and methane (CH 4 ).…”
Section: R Spahni Et Al: Simulation Of Carbon and Nitrogen Dynamicsmentioning
confidence: 99%
“…A blanket peatland map was produced by combining the mapped area of blanket peatlands from the soil survey map for England and Wales (NATMAPvector, 1:250 000) and Scotland (National Soils Map, NSM, 1:250 000) (as described fully in Clark et al 2010). In England and Wales, peat soils meet both of the following criteria: (1) either > 40 cm of organic material is found within the upper 80 cm of the soil profile, or > 30 cm of organic material rests directly on bedrock or skeletal material; and (2) no superficial non-humose mineral horizons with a colour value of 4 or more that extends below 30 cm depth (Clayden & Hollis 1984).…”
Section: Blanket Peatland Mapsmentioning
confidence: 99%
“…4) are consistent with results from previous bioclimatic envelope modelling for blanket peatlands. Both Gallego-Sala et al (2010) and Clark et al (2010) demonstrated that the geographical distribution of bioclimatic space suitable for blanket peatlands may gradually retreat towards the north and west of Great Britain. The low rate of the relative change and the absolute value of mean annual erosion at site 7 do not follow the general spatial pattern across Great Britain.…”
Section: The Future Of Blanket Peat Erosion In Great Britain Under CLmentioning
confidence: 99%
“…PET was calculated with a temperature-based model originally proposed by Oudin et al (2005). The model was modified to include wind speed and vegetation height, as used in the blanket peatland PET estimation by Clark (2005) for our study site 7 (see Fig. 1).…”
Section: Climate Datamentioning
confidence: 99%